Galectin-3 Inhibition Ameliorates Streptozotocin-Induced Diabetic Cardiomyopathy in Mice - Zhu, Ning; Zhu, Liuyan; Huang, Bingwu; Xiang, Wenjun; Zhao, Xuyong (Frontiers in Cardiovascular Medicine, 2022)
Objective Diabetic cardiomyopathy (DCM), characterized by cardiomyopathy with the absence of coronary artery disease, hypertension, and valvular heart disease in patients with diabetes, significantly increases the risk of heart failure. Galectin-3 (Gal-3) has been shown to regulate cardiac inflammation and fibrosis, but its role in DCM remains unclear. This study aimed to determine whether Gal-3 inhibition attenuates DCM and NF-κB p65 activation. Methods DCM was established by i.p. injection of streptozotocin for 5 consecutive days in mice. Myocardial injury markers, such as creatinine kinase MB isoenzyme and lactate dehydrogenase, were detected using ELISA. We used noninvasive transthoracic echocardiography to examine cardiac structure and function. Histological staining was used to explore myocardial morphology and fibrosis. Profibrotic markers and inflammatory cytokines were detected by ELISA and real-time PCR in vivo. TUNEL and immunofluorescence assay were conducted to examine myocardial apoptosis and oxidative stress. Inflammatory cytokines induced by high glucose (HG) were also found in RAW264.7 macrophages. The underlying molecular mechanisms were determined using immunofluorescence and Western blotting analyses. Results Gal-3 knockdown was observed to ameliorate myocardial apoptosis, oxidative stress, inflammatory cytokines release, macrophage infiltration, and fibrosis, thus decreasing cardiac dysfunction in DCM mice. In addition, the silence of Gal-3 could suppress macrophage infiltration and inflammatory cytokine release induced by HG. Finally, a Gal-3/NF-κB p65 regulatory network was clarified in the pathogenesis of DCM. Conclusions Gal-3 may promote myocardial apoptosis, oxidative stress, inflammation and fibrosis in vivo and in vitro by the mechanism of reduction of NF-κB p65 activation.